2021
DOI: 10.1098/rsta.2020.0109
|View full text |Cite
|
Sign up to set email alerts
|

Stress minimization for lattice structures. Part I: Micro-structure design

Abstract: Lattice structures are periodic porous bodies which are becoming popular since they are a good compromise between rigidity and weight and can be built by additive manufacturing techniques. Their optimization has recently attracted some attention, based on the homogenization method, mostly for compliance minimization. The goal of our two-part work is to extend lattice optimization to stress minimization problems two-dimensionally. The present first part is devoted to the choice of a parametrized periodicity cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The microscopic initial stress tensor e describes how the macroscopic strain ε is distributed in unit cell Y. We note that (18) already takes stress amplification (see Ferrer et al 2021) into account. The macroscopic strain is given as solution of the macroscopic constitutive equation…”
Section: Bucklingmentioning
confidence: 99%
“…The microscopic initial stress tensor e describes how the macroscopic strain ε is distributed in unit cell Y. We note that (18) already takes stress amplification (see Ferrer et al 2021) into account. The macroscopic strain is given as solution of the macroscopic constitutive equation…”
Section: Bucklingmentioning
confidence: 99%
“…The inconvenience is that this process is computationally expensive since the cell problem should be solved for as many microstructures to characterize the parametric domain. See for example, Ferrer et al (2021).…”
Section: Using Topological Derivative Within a Relaxed Formulationmentioning
confidence: 99%
“…A few studies have focused on improving microstructure strength, including stress minimisation and buckling strength optimisation. It has been shown that the maximum von Mises stress can be reduced when taking stress into account during the microstructure optimisation procedure either as constraints or objectives (Collet et al, 2018;Coelho et al, 2019;Alacoque et al, 2021;Ferrer et al, 2021). The stress singularity issue, where the stress at a point approaches infinity as the density at that point approaches zero, was handled by stress relaxation methods (Cheng and Guo, 1997;Duysinx and Bendsøe, 1998;Bruggi, 2008;Le et al, 2010).…”
Section: Introductionmentioning
confidence: 99%